2021
DOI: 10.1021/acsami.1c09682
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modification of Palladium Catalysts with Chain Alkylamines for the Selective Hydrogenation of Alkynes

Abstract: Selective hydrogenation of alkynes plays a pivotal role in the field of chemical production but still suffers from restrained catalytic activity and low alkene selectivity. Herein, a dynamic modification strategy was utilized by preferentially attaching diethylenetriamine (DETA) to the surface of the support to modify the Pd catalyst. The DETA-modified Pd catalyst demonstrates unprecedented reactivity (14,412 h −1 ) and selectivity as high as 94% for the semihydrogenation of 2-methyl-3-butyn-2-ol at 35 °C, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 62 publications
1
35
0
2
Order By: Relevance
“…Currently, many studies have demonstrated that the supports have a large influence on the catalytic performance of metal NPs. , For example, metal NPs governed the dissociation of H 2 , while reducible oxide supports adsorbed the reactants . Similar processes were found in metal NP/MOF (MOF: metal–organic framework) composites with metal nodes of MOFs acting as the adsorption sites for reactants and metal NPs serving as the sites for H 2 dissociation .…”
Section: Introductionmentioning
confidence: 92%
“…Currently, many studies have demonstrated that the supports have a large influence on the catalytic performance of metal NPs. , For example, metal NPs governed the dissociation of H 2 , while reducible oxide supports adsorbed the reactants . Similar processes were found in metal NP/MOF (MOF: metal–organic framework) composites with metal nodes of MOFs acting as the adsorption sites for reactants and metal NPs serving as the sites for H 2 dissociation .…”
Section: Introductionmentioning
confidence: 92%
“…Copyright 2022, Tsinghua University Press. Panels (c), (e), and (f) have been reproduced with permission from refs (Copyright 2019, Royal Society of Chemistry, London) and (Copyright 2021, American Chemical Society, Washington, DC). ]…”
Section: The Geometric and Electronic Effects For Selective Hydrogena...mentioning
confidence: 99%
“…Currently, Pd-based heterogeneous catalysts, such as Lindlar 4,5 and Pd–Ag alloys, 6 are widely used in this reaction because of their physico–chemical properties and high activity, but the limited selectivity to the desired alkenes remains a challenge, especially at high conversion. 7,8 Hence, the development of effective strategies for improving the selectivity of Pd catalysts without compromising the activity has attracted broad interest.…”
Section: Introductionmentioning
confidence: 99%